Fatores que contribuem para utilização de indicadores de responsabilidade social: um estudo de caso na Masisa S.A. - Pereira, Viviane Maravieski (2008)
Nowadays the Corporate Social Responsibility has been seen as a competitive differential strategy to organizations and investing in actions and programs to develop the society as well as the environment in which it acts has demanded business replanning. Measuring the action results in order to manage this process is not an easy task that is why the number of companies which have been using social responsibility indicators is seen as increasing. This paper’s aim is to identify the factors or motivations which lead the investigated company to use social responsibility indicators. The method used to research was inductive. The exploratory character research is characterized as a case study. The study has been carried out in the company Masisa S.A., which has been selected according some criteria such as: company size, location as well as structural organization. At theoretical level the main aspects which encircle the topic were approached. Data was collected supported by the following tools: semi-structured interview, documental analysis and direct observation. There were wrapped six collaborators from distinct areas selected by the own company, who were considered prepared enough to contribute with the subject. The method used to the interview inferences was the content qualitative analysis. The results indicate that the collaborators present a positive view concerning the use of social responsibility indicators and the essential contributing factors are that they improve the social management, provide a more reliable management, and because of them it is possible to report the results of the actions as well as social programs and compare them periodically.